Analisis kinerja keuangan dengan rasio likuiditas, rasio aktivitas, rasio hutang dan rasio profitabilitas - Aden Apandi; Fanisyah Maliki; Farmansyah Maliki (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2024)
This research aims to determine the financial performance of PT. TBT, Tbk from 2020 to 2022. The methodology used is documentation in the form of financial report data obtained from the official website of the Indonesia Stock Exchange. Analysis is carried out through calculating four types of ratios. The ratio in question is the liquidity ratio represented by the Current Ratio (CR) and Quick Ratio (QR). Then the second is the activity ratio represented by Inventory Turnover (ITO), Average Collection Period (ACP), Average Payment Period (APP), and Total Asset Turnover (TATO). Third, the solvability ratio is represented by the Debt Ratio (DR) and Times Interest Earned Ratio (TIE). And the last ratio is the Profitability Ratio which is represented by Gross Profit Margin (GPM), Operating Profit Margin (OPM), Net Profit Margin (NPM), Return on Total Assets (ROA), Return on Common Equity (ROE). Results of research and analysis of PT's financial reports. TBT, Tbk from 2020 to 2022, it is known that based on the company's current ratio and quick ratio it has decreased every year. In terms of activity ratios, it can be seen that ITO has experienced a significant increase, ACP in the form of days has decreased, while APP has experienced fluctuations, and TATO has experienced a significant increase. Then the debt ratio, both seen from the company's DR and TIE, experiences fluctuations. Regarding the profitability ratio itself, if we look at the company's GPM, it has experienced a significant decline. Then if you look at OPM, NPM, ROA and ROE, the company experiences fluctuations every year.